PELAKSANAAN PERMOHONAN KASASI JAKSA PENUNTUT UMUM TERHADAP AMAR PUTUSAN BEBAS TINDAK PIDANA KORUPSI - Munir, Miftakhul (Fakultas Hukum Universitas Muhammadiyah Magelang, 2014)
Juridical analysis of the legal proceedings by the public prosecutor against the acquittal (vrijspraak) pursuant to Section 244 Criminal Procedure Code can be concluded that the attorney general penunutut could not bring a legal action in the form of an appeal to the Supreme Court, but there are additional guidelines implementing the Criminal Procedure Code, in item 19 on the attachment the justice minister's decision waives Section 244 Criminal Procedure Code Giving rise to various interpretations or multiple interpretations that add to the ambiguous essence of acquittal. Based on this consideration we conduct research to take the title